YOUTUBE SEBAGAI RUANG PUBLIK ALTERNATIF BAGI ANAK MUDA - Syahirul Alim; Avicena Farkhan Dharma (President University, 2021)
It is undeniable that social media does bring new euphoria, excitement, and ease to society. A recent mode of social interaction exists to facilitate communication between humans, including the consumption of information and the delivery of political aspirations. The pattern of media consumption by young people in the last 10 years has shifted from conventional media to digital platforms such as Twitter and YouTube. This change has spurred the presence of several Internet-based alternative media, one of which is the Asumsi.co YouTube channel. This study aims to describe how young people perceive the content of Asumsi.co YouTube channel as a virtual public space and how Asumsi.co carries out political literacy through video content uploaded to YouTube. By using a descriptive qualitative approach and data collection methods in the form of semi-structured interviews with several young people selected as informants and document analysis, this study resulted in several findings. First, young people interpret the YouTube channel Asumsi.co as an alternative media capable of presenting political information in a comprehensive, progressive, and representative manner. Second, young people feel that political information presented through the YouTube platform can create a deliberative space that can reduce information uncertainty, misinformation, and as a reference in forming personal political opinions. Third, the informants agreed that the virtual sphere can create alternative public spaces for society in particular.